PROBLEMS OF HUMANISM IN THE WORKS OF ABU NASR FARABI (Scientific journal of the Fergana State University, 2024)
This article analyzes that in the views of Abu Nasr Farabi, man was assessed as a being of the highest level, and in his works, the happiness and well-being of people is in harmony and cooperation.